A novel continuous carbon nanotube fiber/carbon composite by electrified preform heating chemical vapor infiltration. (February 2020) - Feng, Lei; Fu, Qiangang; Song, Qiang; Yang, Yanling; Zuo, Yu; Suo, Guoquan; Hou, Xiaojiang; Zhang, Li; Ye, Xiaohui
Abstract: The extraordinary mechanical and physical properties of carbon nanotubes (CNTs) have provided the impetus in developing a new promising CNT/carbon (CNT/C) composite, which may effectively alleviate the shortcomings of sharp-angle and thin-walled C/C components in mechanical performance. Present researches on preparing CNT/C composites focus on infiltrating pyrocarbon into CNT assemblies such as array, block, sheet, film, and buckypaper using complicated and time-consuming methods. Here, we report a facile and efficient strategy for preparing CNT fiber/C composites via electrified preform heating chemical vapor infiltration. Densification process is identified as continual deposition of pyrocarbon around CNTs (called coaxial structure) and further deposition among them, which can be accomplished in short time. Small-diameter (below 500 nm) coaxial structures give composites high deformability; larger ones coupled with bridging action of pyrocarbon among them result in better load transfer and more conductive pathways. Optimized CNT fiber/C composites demonstrate impressive tensile strength (205 MPa) and excellent conductivity (431 S/cm), which are comparable to the previously reported C/C and CNT/C composites. Moreover, such composites exhibit lightweight (1.21 g/cm 3 ), good deformability and high fracture strain. Our work could open up a general strategy for efficiently fabricating various high-performance CNT/C composites that could be used in high-temperature aerospace fields. Graphical abstract: Image 1